Application of SMES Unit to Improve the Performance of Wind Turbine Conversion System - Yunus, A.; Abu-Siada, Ahmed; Masoum, Mohammad Sherkat (Elixir, 2011)
The amount of wind turbine connected to the power grid has significantly increased during the last decade. This has resulted in essential need to establish grid codes. Previously, wind turbine generators (WTGs) were allowed to be disconnected from the network during any disturbance at the grid side to avoid WTGs from being damaged. However, lately, the transmission system operators (TSOs) require WTGs to be stayed connected to provide support to the grid during fault. This new requirement has been regulated in the new grid codes. In this paper, the super conducting magnetic energy storage (SMES) unit is used to enhance the high voltage ride through (HVRT) capability of DFIG based WTG during voltage swell events at the grid side. Two new grid codes are used to verify the ability of the SMES unit to avoid the WTG from being disconnected from the grid.